(untitled) - Roger Leslie Timings (1927- (London, 1995)
This companion volume to volume 1 continues the comprehensive coverage of alloy steels, heat treatment, corrosion and its prevention, and synthetic adhesives. Of particular interest are chapters 7 and 8 which deal with the electrical and electronic properties of materials, and the manufacture of semiconductor materials and devices
Keywords: materials science